(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The Inter-American Court of Human Rights has developed extensive jurisprudence on the rights of indigenous and tribal peoples in which it has recognized the right of these peoples to collective property over land and traditional territory, through an extensive and evolutionary interpretation of the rights of the American Convention on Human Rights (ACHR). We argue that the Court’s jurisprudence on indigenous rights leads to a strong connection with the human right to science and the relationship between both rights can contribute to strengthening and expanding the evolutionary interpretation of the Inter-American Court.